Foreign Ownership and Strike Activity in Canada - Cousineau, J.-M.; Lacroix, R.; Vachon, D. (Relations industrielles / Industrial Relations, 1991)
This microeconomic study of strike activity adds to an already tested empirical strike model, variables that are related to foreign-owned firms in Canada. AU results converge to the same and unique conclusion: foreign-owned firms in Canada show a lower strike propensity, everything else being constant. Such a result suggests that multinational firms may well develop bargaining "protocoles" that overcompensate problems of credibility and information expected to be associated with foreign-owned property.